(1 point) By dragging statements from the left column to the right column below, give a proof by induction of the following statement: For all n≥0, 1+2+22+ +2=2n+1-1. The correct proof will use 8 of the statements below. Statements to choose from: Now assume that P(k) is true for an arbitrary integer k ≥ 0. Therefore, by the Principle of Mathematical Induction, P(n) is true for all n ≥ 0. Then 1+2+22 ·+2k+1 =2 (1+2+2² + ... +2k) =2(2k+1-1) =2(k+1)+1-1 Your Proof: Put chosen statements in order in this column and press the Submit Answers button. Then 1+2+22+ +2k+1 =2k+1 - 1+2k+1 = 2.2k+1-1 =2k+2 - 1 =2(k+1)+1-1 Note that 1+2+22+.... +2k+1 (1+2+2+2)+2k+1. Thus P(k+1) is true. Thus P(k) is true for all k. = Observe that 1=20+1 - 1. So P(0) is true. Then k(k+1)(2k+1) 12+22+1 +(k+1)²= by 6 the inductive hypothesis. Now assume that P(k + 1) is true for all k. Note that 1+2=21+1 - 1 = 3. Then 1+2+22+...+2 = 2k+1 - 1. Let P(n) be the predicate, *1+2+2² + +2=2n+1-1".

College Algebra (MindTap Course List)
12th Edition
ISBN:9781305652231
Author:R. David Gustafson, Jeff Hughes
Publisher:R. David Gustafson, Jeff Hughes
Chapter8: Sequences, Series, And Probability
Section8.5: Mathematical Induction
Problem 43E
icon
Related questions
Question
Not use ai please
(1 point)
By dragging statements from the left column to the right column below, give a proof by induction of the following statement:
For all n≥0, 1+2+22+
+2=2n+1-1.
The correct proof will use 8 of the statements below.
Statements to choose from:
Now assume that P(k) is true for an arbitrary
integer k ≥ 0.
Therefore, by the Principle of Mathematical
Induction, P(n) is true for all n ≥ 0.
Then
1+2+22 ·+2k+1
=2 (1+2+2² + ... +2k)
=2(2k+1-1)
=2(k+1)+1-1
Your Proof: Put chosen statements in order in this
column and press the Submit Answers button.
Then
1+2+22+
+2k+1
=2k+1 - 1+2k+1
= 2.2k+1-1
=2k+2 - 1
=2(k+1)+1-1
Note that 1+2+22+....
+2k+1
(1+2+2+2)+2k+1.
Thus P(k+1) is true.
Thus P(k) is true for all k.
=
Observe that 1=20+1 - 1. So P(0) is true.
Then
k(k+1)(2k+1)
12+22+1
+(k+1)²=
by
6
the inductive hypothesis.
Now assume that P(k + 1) is true for all k.
Note that 1+2=21+1 - 1 = 3.
Then 1+2+22+...+2 = 2k+1 - 1.
Let P(n) be the predicate,
*1+2+2² +
+2=2n+1-1".
Transcribed Image Text:(1 point) By dragging statements from the left column to the right column below, give a proof by induction of the following statement: For all n≥0, 1+2+22+ +2=2n+1-1. The correct proof will use 8 of the statements below. Statements to choose from: Now assume that P(k) is true for an arbitrary integer k ≥ 0. Therefore, by the Principle of Mathematical Induction, P(n) is true for all n ≥ 0. Then 1+2+22 ·+2k+1 =2 (1+2+2² + ... +2k) =2(2k+1-1) =2(k+1)+1-1 Your Proof: Put chosen statements in order in this column and press the Submit Answers button. Then 1+2+22+ +2k+1 =2k+1 - 1+2k+1 = 2.2k+1-1 =2k+2 - 1 =2(k+1)+1-1 Note that 1+2+22+.... +2k+1 (1+2+2+2)+2k+1. Thus P(k+1) is true. Thus P(k) is true for all k. = Observe that 1=20+1 - 1. So P(0) is true. Then k(k+1)(2k+1) 12+22+1 +(k+1)²= by 6 the inductive hypothesis. Now assume that P(k + 1) is true for all k. Note that 1+2=21+1 - 1 = 3. Then 1+2+22+...+2 = 2k+1 - 1. Let P(n) be the predicate, *1+2+2² + +2=2n+1-1".
Expert Solution
steps

Step by step

Solved in 2 steps

Blurred answer
Recommended textbooks for you
College Algebra (MindTap Course List)
College Algebra (MindTap Course List)
Algebra
ISBN:
9781305652231
Author:
R. David Gustafson, Jeff Hughes
Publisher:
Cengage Learning
Algebra & Trigonometry with Analytic Geometry
Algebra & Trigonometry with Analytic Geometry
Algebra
ISBN:
9781133382119
Author:
Swokowski
Publisher:
Cengage
Elements Of Modern Algebra
Elements Of Modern Algebra
Algebra
ISBN:
9781285463230
Author:
Gilbert, Linda, Jimmie
Publisher:
Cengage Learning,
College Algebra
College Algebra
Algebra
ISBN:
9781337282291
Author:
Ron Larson
Publisher:
Cengage Learning